2003
DOI: 10.1007/s10209-003-0057-7
|View full text |Cite
|
Sign up to set email alerts
|

Issues surrounding the user-centred development of a new interactive memory aid

Abstract: Memory problems are often associated with the ageing process and are one of the commonest effects of brain injury. Electronic memory aids have been successfully used as a compensatory approach to provide reminders to individuals with prospective memory problems. This paper describes the usability issues surrounding the development of a new memory aid rendered on a personal digital assistant (PDA); in addition, it discusses the importance of a user-centred design process for the development of the memory aid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 54 publications
(37 reference statements)
1
21
0
1
Order By: Relevance
“…Aural or visual reminders to perform a given task at a particular time included: Voice recorders with a timer function (van den Broek, Downes, Johnson, Dayus, & Hilton, 2000;Yasuda et al, 2002); text messaging to mobile phones (Pijnenborg, Withaar, Evans, van den Bosch, & Brouwer, 2007), voice messages to phones (Leirer, Morrow, Tanke, & Pariante, 1991), reminder functions on a smartphone (Svoboda & Richards, 2009) or schedule software on a PC (Flannery, Butterbaugh, Rice, & Rice, 1997;Kim, Burke, Dowds, & George, 1999;Kim, Burke, Dowds, Boone, & Park, 2000) and PDA (Davies, Stock, & Wehmeyer, 2002;Ferguson, Myles, & Hagiwara, 2005;Giles & Shore, 1989;Gillette & Depompei, 2008;Inglis et al, 2003;Sablier, Stip, Franck, & Mobus Group, 2010).…”
Section: Higher-level Cognitive Functions (B164 58 Studies)mentioning
confidence: 99%
“…Aural or visual reminders to perform a given task at a particular time included: Voice recorders with a timer function (van den Broek, Downes, Johnson, Dayus, & Hilton, 2000;Yasuda et al, 2002); text messaging to mobile phones (Pijnenborg, Withaar, Evans, van den Bosch, & Brouwer, 2007), voice messages to phones (Leirer, Morrow, Tanke, & Pariante, 1991), reminder functions on a smartphone (Svoboda & Richards, 2009) or schedule software on a PC (Flannery, Butterbaugh, Rice, & Rice, 1997;Kim, Burke, Dowds, & George, 1999;Kim, Burke, Dowds, Boone, & Park, 2000) and PDA (Davies, Stock, & Wehmeyer, 2002;Ferguson, Myles, & Hagiwara, 2005;Giles & Shore, 1989;Gillette & Depompei, 2008;Inglis et al, 2003;Sablier, Stip, Franck, & Mobus Group, 2010).…”
Section: Higher-level Cognitive Functions (B164 58 Studies)mentioning
confidence: 99%
“…Computer systems allow central storage of schedules to be delivered as text prompts at the point when a behaviour requires to be carried out. The effectiveness of pager-type prompting, as provided by MemoJog (Inglis et al, 2003) and Neuropage (Wilson, Emslie, Quirk, and Evans, 2001), has been demonstrated to increase achievement of target behaviours. Similarly the MEMEX project, utilising text messaging to mobile phones, has demonstrated effectiveness in improving attendance at appointments and medication compliance (Pijnenborg, Withaar, Evans, van den Bosch, and Brouwer, 2007).…”
mentioning
confidence: 99%
“…Attentional function predicts use of cognitive aids in sample of people with acquired brain injury (Evans et al, 2003). Yet the main ATC systems, such as Neuropage (Wilson, Evans, Emslie, and Malinek, 1997), MemoJog (Inglis et al, 2003), and Pocket Coach (Gentry et al, 2008) Voice Mediated Assistive Technology for Cognition 8 require users to interact with the ATC via a screen. Users usually receive information via the screen, and give feedback to the device via the screen.…”
mentioning
confidence: 99%
“…A small number of published papers directly address these issues [e.g. 2,3] and some papers mention challenges of working with these user groups in passing.…”
Section: Methods For Undertaking Research On Technology With Older Anmentioning
confidence: 99%